Regeneration of macronutrients and trace metals during phytoplankton decay: An experimental study. (5th March 2020) - Hollister, Adrienne P.; Kerr, Makenzie; Malki, Kema; Muhlbach, Eric; Robert, Maya; Tilney, Charles L.; Breitbart, Mya; Hubbard, Katherine A.; Buck, Kristen N.
Abstract: Macronutrients and trace metals are incorporated into phytoplankton during growth and regenerated back into the water column when phytoplankton decay, a process that contributes to the distributions of dissolved trace metals and macronutrients in depth profiles. To study this, we incubated mixed Gulf of Mexico phytoplankton assemblages and monocultures of the diatom Pseudo‐nitzschia dolorosa and the dinoflagellate Karenia brevis in the dark. Over 6 months, macronutrients (phosphate, silicic acid, nitrate + nitrite, nitrite, ammonium), chlorophyll‐ a, particulate organic carbon and nitrogen, and prokaryotes were monitored alongside dissolved manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), cadmium (Cd), and lead (Pb). Results were compared to depth profiles to evaluate the role of regeneration in trace metal cycling. In contrast to water‐column distributions, silicic acid and phosphate were closely coupled in experiments containing diatoms, indicating a shared regeneration pathway. Nitrification and nitrifying prokaryotes were only observed near the end of a subset of the experiments. Of the trace metals, Cd was most tightly coupled with phosphate. Regeneration of Mn was followed by rapid drawdown, consistent with Mn‐oxide formation. Iron (Fe), Cu, and Pb typically remained low until Mn was depleted, suggesting either scavenging to Mn‐oxides or otherwise delayed regeneration of these elements. Cobalt (Co) and Ni were largely conservative, but behaved like nutrients in the experiment using more offshore water low in Cd and Zn. Although experimental conditions were limited in their representation of the water column, these incubations provide novel insight into macronutrient and trace metal regeneration in the oceans.